2015
DOI: 10.1038/nature14600
|View full text |Cite
|
Sign up to set email alerts
|

Viral-genetic tracing of the input–output organization of a central noradrenaline circuit

Abstract: Deciphering how neural circuits are anatomically organized with regard to input and output is instrumental in understanding how the brain processes information. For example, locus coeruleus norepinephrine (LC-NE) neurons receive input from and send output to broad regions of the brain and spinal cord, and regulate diverse functions including arousal, attention, mood, and sensory gating1–8. However, it is unclear how LC-NE neurons divide up their brain-wide projection patterns and whether different LC-NE neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
647
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 657 publications
(668 citation statements)
references
References 40 publications
18
647
3
Order By: Relevance
“…Our proof-of-principle application of RC::FLTG and RC::RFLTG to analysis of the central noradrenergic system confirms the value of key features of these alleles. There are no molecular markers known to uniquely label subpopulations of noradrenergic neurons, so investigation of noradrenergic neuron heterogeneity, particularly axon projection patterns, depends either on genetic intersectional labeling (Robertson et al, 2013) or strategies for retrograde labeling by injection of dyes or viruses at target sites (Chandler and Waterhouse, 2012;Chandler et al, 2013Chandler et al, , 2014Schwarz et al, 2015). The ability of RC::FLTG to label axons of the entire noradrenergic system, subdivided between an intersectional and a subtractive population, reveals diversity of noradrenergic projections at target sites.…”
Section: Discussionmentioning
confidence: 99%
“…Our proof-of-principle application of RC::FLTG and RC::RFLTG to analysis of the central noradrenergic system confirms the value of key features of these alleles. There are no molecular markers known to uniquely label subpopulations of noradrenergic neurons, so investigation of noradrenergic neuron heterogeneity, particularly axon projection patterns, depends either on genetic intersectional labeling (Robertson et al, 2013) or strategies for retrograde labeling by injection of dyes or viruses at target sites (Chandler and Waterhouse, 2012;Chandler et al, 2013Chandler et al, , 2014Schwarz et al, 2015). The ability of RC::FLTG to label axons of the entire noradrenergic system, subdivided between an intersectional and a subtractive population, reveals diversity of noradrenergic projections at target sites.…”
Section: Discussionmentioning
confidence: 99%
“…canine adenovirus type 2 or "CAV-2") that engage CAR as an attachment molecule, circumstantial evidence suggests that CAR is not expressed by all neuron subtypes. We have previously shown that CAV-2 vectors infect motor, cholinergic, dopamine, melanin-concentrating hormone, noradrenergic neurons, 8,9 and all available evidence suggest that CAV-2 vector infection depends on CAR expression. [10][11][12] In contrast to the transcellular interaction in epithelial cells, we showed that when CAR is at the synapse of mature neurons, it is exclusively pre-but not post-synaptic.…”
mentioning
confidence: 98%
“…Although the anatomical studies reveal that distinct LC neurons project to specific brain regions, other studies using a variety of anatomical approaches have found that LC neurons are homogenous and exhibit more collateralization in their efferent connectivity (Nakamura and Iwama 1975;Nagai et al 1981;Room et al 1981;Schwarz et al 2015). It will be important in future work to determine the degree of collateralization and specificity individual populations of LC neurons exhibit in their efferent connectivity.…”
Section: Anatomical Connectivity and Efferent Specificity In Lc Neuronsmentioning
confidence: 98%
“…For example, it hinges on the idea that different subpopulations of LC neurons project to amygdala and mPFC and that they serve distinct functions during different types of learning. However, there are many studies which report highly collateralized projection patterns of LC neurons (Nakamura and Iwama 1975;Nagai et al 1981;Room et al 1981;Schwarz et al 2015) and it is not clear whether specific subpopulations of cells project to these regions or even, more generally, whether distinct behaviorally functional subclasses of LC neurons exist. Furthermore, this model may be too general.…”
Section: A Hypothetical Model Of Lc Function During Learning and Memorymentioning
confidence: 99%